Renal and Neurologic Benefit of Levosimendan vs Dobutamine in Patients With Low Cardiac Output Syndrome After Cardiac Surgery: Clinical Trial FIM-BGC-2014-01 - Guerrero-Orriach, Jose L.; Malo-Manso, Alfredo; Ramirez-Aliaga, Marta; Florez Vela, Ana Isabel; Galán-Ortega, Manuel; Moreno-Cortes, Isabel; Gonzalez-Almendros, Inmaculada; Ramirez-Fernandez, Alicia; Ariza-Villanueva, Daniel; Escalona-Belmonte, Juan Jose; Quesada-Muñoz, Guillermo; Sepúlveda-Haro, Enrique; et al. (Frontiers in Pharmacology, 2020)
Abstract: Background: Low cardiac output syndrome (LCOS) after cardiac surgery is related to systemic hypoperfusion and is associated with a higher incidence of renal and neurological impairment. LCOS can be effectively treated with different drugs. Levosimendan may have systemic effects even though cardiac output is restored, which suggests an independent cardioprotective effect. Methods: A double-blind clinical trial was conducted. Patients with a confirmed diagnosis of LCOS were randomized into two treatment groups (levosimendan vs. dobutamine). At diagnosis and over the following 48 hours, haemodynamic (cardiac index, systolic volume index, heart rate, mean arterial pressure, central venous pressure, central venous saturation); biochemical (e.g. creatinine, S100B protein, NT-proBNP, troponin I); and renal parameters, acute kidney injury scale (AKI scale) and renal and brain ultrasound measurements: vascular resistances index (VRI) were recorded. Results: Initially, significant differences were observed between groups in terms of cardiac index, systolic volume index, NT-proBNP and renal staging at diagnosis. There were significant variations in the AKI stage after 24 and 48 hours in the levosimendan group. No significant differences were observed in the remaining parameters evaluated. Discussion: Levosimendan showed a beneficial effect on the renal function of LCOS patients after cardiac surgery, regardless of cardiac output and vascular tone. This effect is probably associated with pharmacological postconditioning.